Application of Project Based Learning Model (PjBL) in Learning Design Digital Based Batik Basic Motives at Vocational Schools - Purnawirawan, Okta (Journal of Vocational and Career Education, 2020)
Early learning about the introduction of batik to students is very appropriate that batik is not forgotten. Learning the making of basic batik motifs in vocational school (SMK) students is a form of batik conservative activity for children. Learning in vocational students about making digital-based batik basic motifs is very appropriate because it is to equip additional hard skills when they graduate as one of the opportunities to work and become entrepreneurs skills. Learning models are needed in a lesson so that goals can be achieved. The appropriate learning model and in accordance with the characteristics of vocational or vocational education, namely PjBL. This model can provide learners with a learning experience in producing a work. In addition, as a learning support, a learning media is needed, the media used is the CorelDraw graphic design application software, which is a computer application software that can be used as a learning medium in making digital-based batik motifs. SMK students can create various types of basic batik motifs using this application software. The tools or menus contained in the CorelDraw graphic design application software are able to assist students in making basic designs of batik motifs. The results showed the effectiveness of the use of graphic design application software CorelDraw in the basic learning of graphic design class ten RPL expertise competency in making digital-based batik basic motifs using the PjBL model of 81.09%.